2002
DOI: 10.1161/01.cir.0000018166.84319.55
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Accelerates Reendothelialization

Abstract: Background-Primary and secondary prevention trials suggest that statins possess favorable effects independent of cholesterol reduction. We investigated whether statin therapy may also accelerate reendothelialization after carotid balloon injury. Methods and Results-Simvastatin treatment in 34 male Sprague-Dawley rats accelerated reendothelialization of the balloon-injured arterial segments (reendothelialized area at 2 weeks, 12.3Ϯ1.8 versus 5.4Ϯ1.1 mm 2 , PϽ0.01) and resulted in a dose-dependent (0.2 or 1 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
329
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 840 publications
(341 citation statements)
references
References 44 publications
6
329
0
6
Order By: Relevance
“…10 -8 M Simvastatin promoted osteogenic activity in vitro [39] Statins increase the number of circulating Endothelial Progenitor Cells (EPCs), accelerate re-endothelalization after carotid ballon myocardial surgery and improve postischemic cardiac function. Statins induce angiogenesis by promoting the proliferation, migration and survival of EPCs [40].…”
Section: Discussionmentioning
confidence: 99%
“…10 -8 M Simvastatin promoted osteogenic activity in vitro [39] Statins increase the number of circulating Endothelial Progenitor Cells (EPCs), accelerate re-endothelalization after carotid ballon myocardial surgery and improve postischemic cardiac function. Statins induce angiogenesis by promoting the proliferation, migration and survival of EPCs [40].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the pleiotropic effects of statins are cholesterol independent, such as improvement of endothelial function, increased NO bioavailability, antioxidant properties, inhibition of inflammatory responses, immunomodulatory actions, upregulation of endothelial nitric oxide synthase (eNOS), decrease of platelet activation, and regulation of progenitor cells. 42,43 Pretreatment of stroke with statins reduces brain infarct size and improves neurological outcome by directly upregulating brain eNOS. 44,45 Combination atorvastatin and recombinant human tissue plasminogen activator (rhtPA) treatment 4 hours after stroke induces downregulation of tissue factor, protease-activated receptor 1, intercellular adhesion molecule 1, and matrix metalloproteinase 9 (MMP 9); concomitantly, it reduces cerebral microvascular thrombosis and enhances microvascular integrity.…”
Section: Pharmacological Treatment Of Stroke Statinsmentioning
confidence: 99%
“…Recent studies have suggested that endothelial progenitor cells (EPCs) may contribute to neovasculogenesis and reendothelialization of damaged blood vessels to maintain the endothelium [2,3] . Some cardiovascular diseases (CVD) and cardiovascular risk factors are associated with lower numbers and dysfunction of circulating EPCs [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%